Thyroglossal cyst – A retrospective analysis in a tertiary care center - Debajit Sarma,; Mridusmita Gohain,; Mubeez Mustafa Badusha,; Shankhadhwaj Borah,; Rupanjita Sangma,; Adity Sharma, (Asian Journal of Medical Sciences, 2024)
Background: Thyroglossal duct cyst (TGDC), one of the most common congenital neck lesions, is due to the persistence and dilatation of remnants of an epithelial tract, formed during migration of the thyroid in embryogenesis. Aims and Objectives: The objective was to study the location of TGDC in different age and sex groups and variations in presentation. Materials and Methods: A retrospective study was carried out in the Department of ENT at Assam Medical College and Hospital, Dibrugarh from July 2018 to June 2023. The diagnosis was made on the basis of fine-needle aspiration cytology and ultrasonography. Results: A total of 25 cases were analyzed. Majority of them belonged to the age group of 11–20 years. Male: female ratio was 2:3. Nearly 100% of cases had a chief complaint of midline neck swelling that moves with protrusion of the tongue. Most common site of occurrence is the infrahyoid region. Nearly 80% of cases underwent Sistrunk operation. Conclusion: Thyroglossal cyst with its varied presentation is notorious for recurrence. Proper evaluation and excision are the keys toward successful outcomes.